Observation of unphosphorylated STAT3 core protein binding to target dsDNA by PEMSA and X‐ray crystallography. Issue 7 (19th February 2013) - Nkansah, Edwin; Shah, Rahi; Collie, Gavin W.; Parkinson, Gary N.; Palmer, Jonathan; Rahman, Khondaker M.; Bui, Tam T.; Drake, Alex F.; Husby, Jarmila; Neidle, Stephen; Zinzalla, Giovanna; Thurston, David E.; et al.
Abstract : pSTAT3βtc and pSTAT3βtc bind by molecular sieving (View interaction) Abstract : ► Stoichiometric uSTAT3 interaction with M67 DNA. ► Interaction is weaker compared to pSTAT3 M67 DNA interaction. ► Report of a novel protein electrophoretic mobility shift assay (PEMSA).